Oil palm contract growing in Sultan Kudarat perspectives of contractees, non-contract growers, and the contractor - Jara, Fritzie Ivy D.
This study analyzed oil palm contract growing in Bagumbayan, Isulan, President Quirino, and Tacurong City in the province of Sultan Kudarat, Southern Philippines. The Contract Farming Framework was used to examine the existing contractual relationship. Econometric analyses were incorporated in the study to supplement the qualitative analysis of one portion the framework, the farmer's side. Logit method was used to analyze the factors that influence farmer's decision to engage in contract farming. In addition, Ordinary Least Square regression was employed in the quantitative analysis to determine the effects of various factors, including participation in contract farming, to per capita income. The results revealed that the roles played by the contractees and the contractor are vital for the success of oil palm contract farming in Sultan Kudarat. Generally, the preconditions of contract farming in the province were identified to be favorable for growing oil palm. Furthermore, farming experience, farmer's age and farm size contributed much to the decision of the farmers to engage in a contract. Per capita income had significant positive correlation with farmer's experience in agricultural activities and the farm size.